Bionic Plasmonic Nanoarrays Excited by Radially Polarized Vector Beam for Metal-Enhanced Fluorescence - Min Liu; Lan Yu; Yanru Li; Ying Ma; Sha An; Juanjuan Zheng; Lixin Liu; Ke Lin; Peng Gao (Nanomaterials, 2023)
Metal-enhanced fluorescence (MEF) is an important fluorescence technology due to its ability to significantly improve the fluorescence intensity. Here, we present a new MEF configuration of the bionic nanorod array illuminated by radially polarized vector beam (RVB). The bionic nanorod array is fabricated via a nanoimprinting method by using the wings of the Chinese cicada “meimuna mongolica” as bio-templates, and later coating gold film by ion sputtering deposition method. The MEF performance of the prepared substrate is tested by a home-made optical system. The experiment results show that, in the case of RVB excitation, the intensity of fluorescence is more than 10 times stronger with the nano-imprinted substrate than that with glass. Using the bionic nanoarray as a substrate, the intensity of fluorescence is ~2 times stronger via RVB than that by the linearly polarized beam. In addition, the prepared substrate is verified to have good uniformity.